Adaptive fuzzy sliding mode control for vibration suppression of a rotating carbon nanotube-reinforced composite beam. (June 2018) - Rahmani, Behrooz
In this paper, the robust vibration control of a rotating carbon nanotube reinforced composite beam subjected to a temperature rise is studied. The governing mathematical partial differential equations are derived by Hamilton's principle based on Euler–Bernoulli beam theory. The Galerkin method is then used to obtain the temporal ordinary differential equations and therefore to perform vibration analysis. For the purpose of vibration control, piezoelectric patches are used as sensors to measure the displacement of the beam and as actuators to implement control forces. A model-free adaptive fuzzy sliding mode controller is utilized to suppress the vibration of the rotating carbon nanotube reinforced composite beam. Since the plant's state vector cannot be measured for control purposes and only the piezoelectric sensor's output is available, a model-free adaptive fuzzy sliding mode observer is proposed here. Simulation studies demonstrate the effectiveness of the proposed method.